2008
DOI: 10.1002/jor.20783
|View full text |Cite
|
Sign up to set email alerts
|

Understanding patellofemoral pain with maltracking in the presence of joint laxity: Complete 3D in vivo patellofemoral and tibiofemoral kinematics

Abstract: Patellofemoral pain is widely accepted as one of the most common pathologies involving the knee, yet the etiology of this pain is still an open debate. Generalized joint laxity has been associated with patellofemoral pain, but is not often discussed as a potential source of patellar maltracking. Thus, the objective of this study was to compare the complete 6 degree of freedom patellofemoral and tibiofemoral kinematics from a group of patients diagnosed with patellofemoral pain syndrome and maltracking to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 41 publications
7
82
2
Order By: Relevance
“…The slope of each variable was defined by the linear best fit of each with knee angle. The validity of using a linear best fit has been documented [39].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The slope of each variable was defined by the linear best fit of each with knee angle. The validity of using a linear best fit has been documented [39].…”
Section: Methodsmentioning
confidence: 99%
“…In one study, no differences were reported [25], yet in another, differences in the majority of the 3D PF displacements and rotations were reported [39]. This variability is likely the result of differences in measurement techniques, variables measured, and the presence of various types of maltracking patterns in the omnibus term of patellar maltracking [37,39]. For example, Schutzer et al [37] identified three distinct malalignment patterns in patients with PF pain: excessive lateral tilt, lateral subluxation, and lateral subluxation with tilt.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations